Intrauterine bony fragments - An unexpected finding in the hysterectomy specimen - Madhu Chaturvedi; Ankita Shende (University of São Paulo, 2021)
Intrauterine bony fragments (IUBF) are an unusual finding in hysterectomy specimen received in a histopathology laboratory. Females harboring IUBF may present non-specific symptoms like vaginal bleeding, leukorrhea, chronic pelvic pain, and secondary infertility. Herein we report the case of a 35-year-old female who presented vaginal discharge and bleeding for two years, since when she had an abortion. Later, hysterectomy specimen revealed bone pieces in the uterine cavity.